Soreness and ulcers 5: biology, diagnosis and management of cancer regimen 2 - Sonis, Stephen T. (Henry Stewart Talks, 2017)
Risk of toxicity, Genomically based risk factors, Candidate genes, Genome wide association studies, Gene/SNP networks